Enhanced separation and characterization of deamidated peptides with RP-ERLIC-based multidimensional chromatography coupled with tandem mass spectrometry - Hao, Piliang (2013)
Deamidation of asparaginyl residues in proteins produces a mixture of asparaginyl, n-aspartyl, and isoaspartyl residues, which affects the proteins’ structure, function, and stability. Thus, it is important to identify and quantify the products to evaluate the effects in biological systems. It is still a challenging task to distinguish between the n-Asp and isoAsp deamidation products in a proteome-wide analysis because of their similar physicochemical properties. The quantification of the isomeric deamidated peptides is also rather difficult because of their coelution/poor separation in reverse-phase liquid chromatography (RPLC). We here propose a RP-ERLIC–MS/MS approach for separating and quantifying on a proteome-wide scale the three products related to deamidation of the same peptide. The key to the method is the use of RPLC in the first dimensional separation and ERLIC (electrostatic repulsion–hydrophilic interaction chromatography) in the second, with direct online coupling to tandem MS. The coelution of the three deamidation-related peptides in RPLC is then an asset, as they are collected in the same fraction. They are then separated and identified in the second dimension with ERLIC, which separates peptides on the basis of both pI and GRAVY values. The coelution of the three products in RPLC and their efficient separation in ERLIC were validated using synthetic peptides, and the performance of ERLIC–MS/MS was tested using peptide mixtures from two proteins. Applying this sequence to rat liver tissue, we identified 302 unique N-deamidated peptides, of which 20 were identified via all three deamidation-related products and 70 of which were identified via two of them.